2011
DOI: 10.5935/1678-9741.20110041
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização miocárdica com circulação extracorpórea; aspectos bioquímicos, hormonais e celulares

Abstract: Revascularização miocárdica com circulação extracorpórea; aspectos bioquímicos, hormonais e celularesOn-pump coronary artery bypass graft surgery: biochemical, hormonal and cellular features This study was carried out at Federal University of São Paulo, Discipline of Cardiovascular Surgery, São Paulo, SP, Brazil. Methods: Eighteen patients underwent on-pump CABG surgery. Mean time of CPB was 80.3 minutes. Hormonal, biochemical and cellular measurements were taken in some time points -preoperatively, immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
5
0
5
Order By: Relevance
“…Dado este foi confirmado no estudo de Gabriel et al (2011) realizado com 18 pacientes submetidos à CRM com utilização da CEC, revelou que houve ativação significante do número de leucócitos durante e após o período de CEC, mantendo-se assim até 48 horas de pós-operatório, chegando a valores de 23.980 mm3.…”
Section: Materials E Métodounclassified
“…Dado este foi confirmado no estudo de Gabriel et al (2011) realizado com 18 pacientes submetidos à CRM com utilização da CEC, revelou que houve ativação significante do número de leucócitos durante e após o período de CEC, mantendo-se assim até 48 horas de pós-operatório, chegando a valores de 23.980 mm3.…”
Section: Materials E Métodounclassified
“…As hemácias, os leucócitos e as plaquetas podem ser profundamente afetadas na CEC, tanto pelo trauma como pelo contato com as superfícies não endoteliais do circuito (3) .…”
Section: Alterações Dos Elementos Do Sangueunclassified
“…A reação inflamatória sistêmica inerente à CEC é responsável por uma variedade de alterações orgânicas, dentre elas o desajuste da concentração sérica de proteínas totais e albumina, desequilíbrio dos níveis séricos dos hormônios tireoidianos e modificações quantitativas e qualitativas quanto aos leucócitos totais, neutrófilos e plaquetas (3) .…”
Section: Leucócitos Plaquetas E Proteínas Totaisunclassified
“…Plashcke et al showed that patients who had undergone CABG and developed delirium had greater levels of cortisol and interleukin-6 [37]. Indeed, CABG is associated with an increased inflammatory response during the early post-operative period [38], activation of white blood cells and a decrease in thyroid hormone levels [39]. A decrease in the levels of iodine-containing thyroid hormones may predispose individuals to cognitive deficits after surgery [40].…”
Section: Delirium After Cardiac Surgery: Specific Risk Factorsmentioning
confidence: 99%